EXSTRACTION-ABSORPTIOMETRIC DETERMINATION OF IRON BY FUCHSINE IN NATURAL AND WASTE WATERS (Proceedings of the YSU B: Chemical and Biological Sciences, 2005)
An interaction of iron(III) chloride anionic complex with threephenylmethane basic dye-fuchsine has been studied. The colored ionic associate could be extracted by dichlorethane (R=0.965) in 6.0–7.0 N hydrochloric acid solutions. The extracts of ionic associate are submitted to be main law of spectrophotometer in the Q.25–6.0 mcg/mL range of iron(III) contents, ε=7.3·104 ± 400 (L·mol–1·cm–1). The molar ratio between iron(III) chloride complex and fuchsine in ionic associate has been determined by method of Asmuse, which (1:1). The influence of interfering elements on the determination of iron has been studied. Method elaborated has been applied for determination of iron in mineral water «Jermuk» and waste waters .
Keywords: threephenylmethane; iron(III) chloride; dye-fuchsine; ionic associate; determination of iron